Isabel Echeverribar - Finite Volume Non-Hydrostatic Pressure (NHP) Model for the Simulation of Landslides - Echeverribar, Isabel (Jornada de Jóvenes Investigadores del I3A, 2022)
Finite Volume Non-Hydrostatic Pressure (NHP) Model for the Simulation of Landslides